The Principles of Biomedical Scientific Writing: Citation - Bahadoran, Zahra (Int J Endocrinol Metab, 2020)
Citation, the act of properly referring to others’ ideas, thoughts, or concepts, is a common and critical practice in scientific writing. Citations are used to give credit to own work, to support an argument, to acknowledge others’ work, to distinguish other authors’ ideas from one’s work, and to direct readers to sources of information. A good citation adds to the scientific prestige of the paper and makes it more valuable to the reader. The citation has three basic elements: quoting from others, an in-text reference to the source, and bibliographic details of the source. Beyond technical skills, the citation needs an in-depth knowledge of the field and should follow basic rules, including the selection of relevant and valid sources, stating information/facts from others’ work, and referring to others’ work accurately and ethically. Several systems and styles are used to cite scientific sources; however, the most commonly used systems in medical sciences are ‘author-date’ systems (e.g., Harvard system) and numerical systems (e.g., Vancouver system). Here, we discuss how to make an accurate, complete, and ethical citation, and provide simple and practical guides to organize references in a scientific medical paper.